The effect of high purity rice husk silica synthesised using solvent-thermal extraction method on the properties of natural rubber compounds - Salim, Zainathul Akhmar Abdul; Hassan, Aziz; Ismail, Hanafi (North Carolina State University, 2018)
This work highlights the synthesis of high purity silica from rice husks and the effect of rice husk silica (RHS) loading on the mechanical, physical, and thermal properties of natural rubber (NR) compounds. The RHS was synthesised using the solvent-thermal extraction method, which was adopted from TAPPI T204 (2007) and TAPPI T264 (1997) standards with some modifications. The treatment successfully produced high purity RHS particles, with 99.9% SiO2 content between 100 to 300 nm in size. The high purity RHS was then incorporated in NR compounds at 2, 4, 6, 8, and 10 parts per hundred rubber (phr). Even without any surface modification, the high purity RHS-filled NR compounds showed tremendous improvements in strength-related properties at the optimum loading of 4 phr. In addition, the thermal stability of the NR compounds was remarkably improved with the addition of RHS. © 2018, BioResources.